Cutaneous manifestations of internal malignancies in a tertiary health care hospital of a developing country Manifestações cutâneas de doenças malignas em um hospital terciário de um país em desenvolvimento - Alex G Ortega-Loayza; Willy Ramos; Ericson L Gutierrez; Patricia Chavez de Paz; Lucia Bobbio; Carlos Galarza (Sociedade Brasileira de Dermatologia, 2010)
In a public hospital in Lima, Peru, 24 patients with 16 types of paraneoplastic dermatoses were identified by data collection. The most frequent dermatosis was dermatomyositis (four patients). The other dermatoses were malignant acanthosis nigricans, palmoplantar keratoderma, bullous dermatoses, lymphomatoid papulosis, edematous scarring vasculitic panniculitis, Norwegian scabies, primary systemic amyloidosis, necrolytic migratory erythema, infective dermatitis, pancreatic panniculitis, generalized pruritus, Lesser-Trelat syndrome, and acquired ichthyosis. Most of these paraneoplastic dermatoses were diagnosed before (45.8%) or at the time of (38.5%) the diagnosis of the underlying malignancy. The most frequent underlying malignancies were lymphoma, adenocarcinomas of the upper digestive tract, and malignant neoplasms of the pancreas. The average age of the patients was 47.0 ± 16.9 years and the length of the disease since diagnosis was 13.7 months. The mortality rate was 75%. Paraneoplastic dermatoses are rare dermatologic entities that are difficult to diagnose. Surveillance is also hampered when patients do not have easy access to health care centers due to financial and geographical issues. However, when identified, they might facilitate the early diagnosis of an associated tumor and contribute to increase the surveillance of patients. Em um hospital público em Lima, Peru, 24 pacientes com 16 tipos de dermatoses paraneoplásicas foram identificados por meio de coleta de dados. A dermatose mais frequente foi dermatomiosite (quatro pacientes). As outras dermatoses foram acantose maligna, queratodermia palmoplantar, dermatoses bolhosas, papulose linfomatóide, cicatriz edematosa, paniculite e vasculite, escabiose norueguesa, amiloidose sistêmica primária, eritema necrolítico migratório, dermatite infecciosa, paniculite pancreática, prurido generalizado, sinal de Leser-Trelat e ictiose adquirida. Grande parte dessas dermatoses foi diagnosticada antes (45,8%) ou no momento (38,5%) do diagnóstico do tumor subjacente. Os tumores malignos mais frequentes foram linfoma, adenocarcinomas do trato digestivo superior e neoplasias malignas do pâncreas. A idade média dos pacientes foi de 47.0 ± 16.9 anos e a duração da doença desde o diagnóstico foi de 13,7 meses. A taxa de mortalidade foi de 75%. Dermatoses paraneoplásicas são condições dermatológicas raras de difícil diagnóstico. O controle também é prejudicado quando pacientes não têm acesso fácil à centros de saúde por questões financeiras ou geográficas. No entanto, quando identificadas, elas podem facilitar o diagnóstico precoce de um tumor associado e contribuir para um aumento do controle dos pacientes.